Ethogram of captive sambar deer Cervus unicolor at Zoo Melaka - Pan, Khang Aun (Department of Wildlife and National Parks - Perhilitan, 1989)
The ethogram of sambar deer (Cervus unicolor) was constructed based on the observations gathered at Zoo Melaka from February to September, 1988. Observations on the herd of 9 sambar deer comprising 3 adult males, 4 adult females and 2 fawns were made in a 4600 m2 circular paddock using both focal and scan sampling techniques. Out of the 10,484 observations made in 345 hours, 9696 or 92.48% were classified as solitary behaviour which included resting, locomotion, grooming, feeding, drinking and elimination. Wild sambar deer are known to be solitary and are seldom found in large herd. The remaining 788 observations (7.52%) were social behaviour. Most of the social behaviours were sexually oriented as there was no distinct breeding season in the sambar. Problems that were related to the classification of behaviour were also discussed.